(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Soil stabilization, process, by which the soil properties are improved, is getting growing attention during last periods. Paper is focused on application for earth structures. Methods of soil stabilization together with their applicability for different soils are discussed firstly. The sensitivity of the process of the cautious estimation of the characteristic values of geotechnical parameters which are subsequently used for the design, is shown on the base of the logical scheme of the geotechnical design report for earth structures. Finally the need of the laboratory tests for the closer specification of the soil stabilization technology and also for the determination of the geotechnical data are discussed.